A randomized phase 1 pharmacokinetic trial comparing the potential biosimilar PF‐05280014 with trastuzumab in healthy volunteers (REFLECTIONS B327‐01)1. (December 2014) - Yin, Donghua; Barker, Kerry B.; Li, Ruifeng; Meng, Xu; Reich, Steven D.; Ricart, Alejandro D.; Rudin, Dan; Taylor, Carrie T.; Zacharchuk, Charles M.; Hansson, Arne G.
<x xml:space="preserve">Abstract</x> Aims The pharmacokinetic (PK) similarity between PF‐05280014, a proposed trastuzumab biosimilar, trastuzumab sourced from European Union (trastuzumab‐EU) or from United States (trastuzumab‐US) was evaluated. Safety and immunogenicity were also assessed. Methods In this phase 1, double‐blind trial (NCT01603264), 105 healthy male volunteers were randomized 1:1:1 to receive a single 6 mg kg−1 intravenous dose of PF‐05280014, trastuzumab‐EU, or trastuzumab‐US, and evaluated for 70 days. Drug concentration–time data were analyzed by non‐compartmental methods. PK similarity for the comparisons of PF‐05280014 to each of trastuzumab‐EU and trastuzumab‐US, and trastuzumab‐EU to trastuzumab‐US were determined using the standard 80.00% to 125.00% bioequivalence criteria. Results Baseline demographics for the 101 subjects evaluable for PK were similar across all arms. The three products exhibited similar PK profiles with target‐mediated disposition. The 90% CIs for the ratios of Cmax, <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgh2cn53mt8" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />AUC(0, tlast)</alternatives> and AUC(0, ∞) were within 80.00% to 125.00% for all three pairwise comparisons. Adverse events (AEs) were similar across all arms with treatment‐related AEs reported by 71.4%, 68.6% and 65.7% subjects in the PF‐05280014, trastuzumab‐EU, and trastuzumab‐US arms, respectively. The most common AEs were infusion‐related reactions, headache, chills, pyrexia and nausea. The AE term 'pyrexia' was numerically greater in the PF‐05280014 arm. All post‐dose samples, except 1, tested negative for anti‐drug antibodies (ADA). Conclusions This study demonstrates PK similarity among PF‐05280014, trastuzumab‐EU and trastuzumab‐US. The safety and immunogenicity profiles observed for the three products in this study are consistent with previous reports for trastuzumab.